Pretreatment of ghrelin protects H9c2 cells against hypoxia/reoxygenation-induced cell death via PI3K/AKT and AMPK pathways. Issue 1 (4th December 2019) - Chen, Yanbo; Wang, Honggang; Zhang, Yong; Wang, Zhengping; Liu, Shanshan; Cui, Lianqun
Abstract: Ghrelin has been widely recognized as a key peptide in the cardiovascular system. This study detected the potential of ghrelin in MI management and tried to decode one of the possible underlying mechanisms. H9c2 cells were pretreated with ghrelin and were subjected to hypoxia/reoxygenation (H/R). CCK-8, flow cytometry, Western blot and LDH analysis were conducted to assess the changes in cell survival. LY294002 and Compound C were used to treat H9c2 cells for blocking PI3K/AKT and AMPK pathways, respectively. Ghrelin expression in H9c2 cells was suppressed by siRNA-mediated silencing to see the effects of endogenous ghrelin. We found that, following H/R, H9c2 cells viability was decreased, CyclinD1 and CDK4 were down-regulated, apoptosis was induced, the release of LDH was enhanced, and the expression levels of Cox-2 and iNOS were up-regulated. Ghrelin protected H9c2 cells against H/R induced these alterations. Besides, ghrelin activated PI3K/AKT and AMPK pathways even in H/R-stimulated cells. The protective effects of ghrelin against H/R-induced cell damage were all attenuated by the addition of LY294002 or Compound C. Moreover, endogenous inhibition of ghrelin significantly induced cell death of H9c2 cells. In conclusion, this study demonstrated that ghrelin pretreatment protected H9c2 cells against H/R-induced cell damage, possibly via PI3K/AKT and AMPK pathways.